(untitled) (Castilla. Estudios de Literatura, 2012)
The technological advances of the last decades have caused an increase in the electronic transfer of information (e-mail, videoconference, short message service, mobile telephony, the blogosphere and such supposedly socially minded web sites as Facebook, Twitter, LinkedIn, etc.) but it remains to be seen whether this will result in increased dialogue, communication, knowledge or critical spirit. These advances have certainly modified habits related to literacy and the literary system, cataloguing methods, publication, literary teaching and theory. And this new context has led to the reconsideration of the production, circulation, reception and interpretation of literary texts, a process that has involved historical, theoretical and aesthetic factors.